Is there really a want of capital in Ireland? - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1851)
The question respecting capital, to which I propose in this paper especially to direct your attention, is the following: ?Is there really a want of capital in Ireland?
A paper read before the statistical section of the British Association, at Ipswich, July 3rd, 1851.
Keywords: Private savings; Poverty; 314.15